Cognitive Computational Neuroscience: A New Conference for an Emerging Discipline. Issue 5 (May 2018) - Naselaris, Thomas; Bassett, Danielle S.; Fletcher, Alyson K.; Kording, Konrad; Kriegeskorte, Nikolaus; Nienborg, Hendrikje; Poldrack, Russell A.; Shohamy, Daphna; Kay, Kendrick
Abstract : Understanding the computational principles that underlie complex behavior is a central goal in cognitive science, artificial intelligence, and neuroscience. In an attempt to unify these disconnected communities, we created a new conference called Cognitive Computational Neuroscience (CCN). The inaugural meeting revealed considerable enthusiasm but significant obstacles remain.